2022
DOI: 10.30574/gscbps.2022.18.3.0098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioactive compound content, in-vitro antioxidant and anti-inflammatory effects of ethanol extract of the seed of Cucumis metuliferus fruit

Abstract: Cucumis metuliferus commonly called Kiwano is a well-known plant in the middle belt area of Nigeria. It is consumed for nutritional and medicinal purposes. This study evaluated the bioactive compound content, In-vitro antioxidant and anti-inflammatory properties of ethanol extract of the seed of Cucumis metuliferus fruit. The antioxidant properties were evaluated using DPPH (2, 2 diphenyl-1-picrylhydrazyl) radical, iron reducing power and inhibition of lipid peroxidation tests. Ascorbic acid served as standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was found that the fruit and seed of Cucumis metuliferus are rich in dietary fiber, vitamin C, and antioxidants, all of which have potential health benefits [25]. The reported antioxidant activity of carotenoids confirms, despite the low value, that the Cucumis metuliferus seed extract is an excellent source of therapeutic compounds [26]. The seeds contain an oil with a high proportion of unsaturated fatty acids, which is rich in carotenoids and tocopherols, and the peel has pharmacological properties, as it contains rutin, miricetin, and quercetin, which are polyphenolic compounds belonging to the chemical category of flavonoids [27].…”
Section: Cucumis Metuliferusmentioning
confidence: 97%
“…It was found that the fruit and seed of Cucumis metuliferus are rich in dietary fiber, vitamin C, and antioxidants, all of which have potential health benefits [25]. The reported antioxidant activity of carotenoids confirms, despite the low value, that the Cucumis metuliferus seed extract is an excellent source of therapeutic compounds [26]. The seeds contain an oil with a high proportion of unsaturated fatty acids, which is rich in carotenoids and tocopherols, and the peel has pharmacological properties, as it contains rutin, miricetin, and quercetin, which are polyphenolic compounds belonging to the chemical category of flavonoids [27].…”
Section: Cucumis Metuliferusmentioning
confidence: 97%